Namibia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues and Statistical Appendix paper analyzes the macroeconomic impact of the HIV/AIDS pandemic, as well as its repercussions on fiscal policy of Namibia. The paper seeks to assess the macroeconomic impact of HIV/AIDS under a successful implementation of Medium-Term Plan III (MTP III) that would lower the prevalence rate to below its 2004 level. The paper also identifies the effect of HIV/AIDS on the real GDP growth rate over the medium term through a source of growth model that estimates the impact of HIV/AIDS on the factors of production.